2017
DOI: 10.1093/icb/icx082
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Potential as a Mechanism of Phenotypic Plasticity in Vertebrate Range Expansions

Abstract: During range expansions, organisms are often exposed to multiple pressures, including novel enemies (i.e., predators, competitors and/or parasites) and unfamiliar or limited resources. Additionally, small propagule sizes at range edges can result in genetic founder effects and bottlenecks, which can affect phenotypic diversity and thus selection. Despite these obstacles, individuals in expanding populations often thrive at the periphery of a range, and this success may be mediated by phenotypic plasticity. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 64 publications
1
48
0
Order By: Relevance
“…Epigenetic variations are molecular modifications that alter gene expression, but not the underlying DNA sequence, and occur in the form of histone modifications, non-coding RNAs, and DNA methylations (Bossdorf et al, 2008;Berger et al, 2009). Recent studies in the young research field of Ecological Epigenetics provide increasing evidence for the potential of epigenetic variation to increase plasticity, facilitate speciation and accelerate adaptation to new environments and stressful conditions (Schrey et al, 2013;Bonasio, 2015;Verhoeven et al, 2016;Kilvitis et al, 2017;Richards et al, 2017).…”
Section: A2 Epigenetic Potential To Adapt To Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic variations are molecular modifications that alter gene expression, but not the underlying DNA sequence, and occur in the form of histone modifications, non-coding RNAs, and DNA methylations (Bossdorf et al, 2008;Berger et al, 2009). Recent studies in the young research field of Ecological Epigenetics provide increasing evidence for the potential of epigenetic variation to increase plasticity, facilitate speciation and accelerate adaptation to new environments and stressful conditions (Schrey et al, 2013;Bonasio, 2015;Verhoeven et al, 2016;Kilvitis et al, 2017;Richards et al, 2017).…”
Section: A2 Epigenetic Potential To Adapt To Climate Changementioning
confidence: 99%
“…Seagrasses likely show methylation in the same three sequence contexts as terrestrial plants, including CHG, CHH, and CG (Xie and Yu, 2015;Kilvitis et al, 2017;Richards et al, 2017). So-called CpG islands represent clusters of CG sites in gene promoter regions, and are commonly associated with gene expression regulation (Bossdorf et al, 2008;Illingworth and Bird, 2009;Zhang and Jeltsch, 2010).…”
Section: A2 Epigenetic Potential To Adapt To Climate Changementioning
confidence: 99%
“…younger populations) expressed more TLR4 than individuals residing nearer to the site of introduction. We also found that house sparrows with lower TLR4 expression were more likely to be infected with malaria and coccidian parasites (Martin et al ) and that high TLR4 expression was associated with low energetic and nutrient costs of inflammation (Martin et al ). These results, collectively, indicate that more TLR4 expression is more protective and/or less costly, but given the broad scope of that previous work, we are reticent to claim that the cause of TLR4 variation among populations or individuals is known.…”
Section: Introductionmentioning
confidence: 81%
“…Already we know that variation in DNA methylation patterns are quite extensive across the geographic range of house sparrows. For example, one non‐commensal subspecies was epigenetically distinct from four commensal subspecies from the Middle East, and overall DNA methylation variation was correlated with some morphological variation (Riyahi et al ). Patterns of DNA methylation also differentiated three distinct introduction events of house sparrows into Australia (Sheldon et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation